MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH PADA DESA CIBITUNG TENGAH, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Trihantana, Rully; Suryani, Ermi; Lestari, Widi (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
The MSME sector plays a very important role in supporting the economy of Cibitung Village. The factors that make it difficult for MSMEs to access Islamic bank financing are that MSME managers do not yet have a good financial management system, manual and traditional business management, and household and company operational funds, so that they cannot be separated. Due to these technical limitations, MSME owners do not really think about business goals and long-term strategic plans. In Cibitung Village in the Bogor Regency area, most of the population still depends on the MSME sector for their livelihoods. This service aims to provide MSME stakeholders with an understanding of financial management, sharia accounts, sharia bank funding rules, financial reporting, and sharia bank funding proposals. The method of implementing this activity is to use the RRA (Rapid Rural Appraisal) method. This assistance has increased our understanding of our partners' material.